2021
DOI: 10.1002/ijc.33609
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐related adverse events predict responses to PD‐1 blockade immunotherapy in hepatocellular carcinoma

Abstract: Immune checkpoint blockade has demonstrated remarkable efficacy in hepatocellular carcinoma (HCC) but is also commonly accompanied by immune‐related adverse events (irAEs). However, the association between irAEs and antitumor efficacy in HCC patients remains unknown. All patients with HCC treated with anti‐PD‐1 antibodies from July 2018 to November 2019 were analyzed and divided into different groups according to their irAEs' status. In total, 101 HCC patients, including 21 (20.8%) patients who presented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
2
11
1
Order By: Relevance
“…In contrast to the above, no difference in serious adverse events was investigated between the TACE and no-TACE groups, which was the same result as in other reports (25,26), indicating the safety of this therapeutic combination. Furthermore, skin rash was reported as a common adverse event with both PD-1 inhibitors and TKIs as tumor therapy, so the treatment response might be related to rash (32), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the above, no difference in serious adverse events was investigated between the TACE and no-TACE groups, which was the same result as in other reports (25,26), indicating the safety of this therapeutic combination. Furthermore, skin rash was reported as a common adverse event with both PD-1 inhibitors and TKIs as tumor therapy, so the treatment response might be related to rash (32), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…A cohort of 101 HBV-HCC patients demonstrated that patients with irAEs such as rash had a much prolonged median PFS and better ORR and DCR than those without. 47 In this study, for the first time, we found that VB may be related to OS and PFS in this population. Notably, unlike the prognostic role of irAEs reported in HCC patients, 47 48 VB was an indicator of poor outcome.…”
Section: Discussionsupporting
confidence: 49%
“…Although the mechanism underlying the occurrence of irAEs is not clear, irAEs have been shown to improve the efficacy of anti-PD-1 antibodies. The occurrence of irAEs has also been reported in liver cancer, especially in patients with rashes and with a significantly longer median PFS ( 24 ). In obese patients, the rate of inflammatory response increases and the probability of irAEs also increases ( 25 , 26 ).…”
Section: Discussion/conclusionmentioning
confidence: 93%